Toxoplasma gondii clonal type III is the dominant genotype identified in Grenadian pigs. Issue 5 (9th July 2022) - Chikweto, Alfred; Alhassan, Andy; Su, Chunlei; Macpherson, Calum; Bhaiyat, Muhammad Iqbal; Dubey, Jitender P.
Abstract: Background: Toxoplasma gondii is a widespread zoonotic protozoan parasite capable of infecting all warm‐blooded animals. Although the genotypes of T. gondii in pigs have been reported worldwide, there is no information on the genotypes and diversity of T. gondii in pigs in Grenada, West Indies. Objectives: The aims of the present study were to isolate, genotype and determine the diversity of T. gondii genotypes in pigs. Methods: We carried out a modified agglutination test (MAT) on blood from 149 pig hearts collected from a local meat market. Myocardial tissue homogenate from pigs that tested positive for T. gondii was homogenized and inoculated into mice for isolation of the parasite. We collected mouse tissues and extracted DNA for genotyping based on 11 polymerase chain reaction‐restriction fragment length polymorphism markers (SAG1, SAG2, alt. SAG2, SAG 3, BTUB, GRA6, L358, PK1, C22‐8, C 29‐2 and Apico). Results: Out of the 149 pig hearts, 31 (20.8%) tested positive for T. gondii on MAT. Bioassays in mice yielded 12 isolates designated TgpgGr1 to TgpgGr12. Molecular characterisation of T. gondii revealed four genotypes as follows: ToxoDB #2‐clonal type III (seven isolates); ToxoDB #7 (three isolates); ToxoDB #13 (one isolate); ToxoDB #30 (1 isolate). Overall, ToxoDB #2 was the most common (58%). Toxo database (DB) # 13, which causes interstitial pneumonia in affected mice, has also been reported. Conclusion: The genetic diversity of T. gondii in pigs in Grenada is lower than that in other surrounding Caribbean areas. Abstract : Isolation and genotyping of Toxoplasma gondii in pigs in Grenada revealed clonal type III as the most common. Phylogenetic analysis using SplitsTree 4.17.1 software indicated that most of the T. gondii isolates were related to the CTG reference strain, a Toxo Db #2 (type III) genotype. The diversity among the T. gondii genotypes was found to be minimal, with clustering of genotypes into two main groups.